KARAKTERISTIK MORFOMETRI DAS CITARIK HULU DAN IMPLIKASINYA TERHADAP POTENSI BANJIR - Pradnya Paramarta Raditya Rendra; Nana Sulaksana (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2021)
The research area is the Upper Citarik Sub Watershed which is located at 107°49’18,1” E-107°57’27,4” E and 6°55’15.7” S-6°59’34.7” S in the Bandung, Sumedang, and Garut Regency. The research aims to identify the morphometric characteristics of the Upper Citarik Sub Watershed and its implication to the flood potential. The research was conducted through studio analysis using thematic maps such as slope and geological map. Several aspects of the watershed morphometry are used to determine the characteristics of the Upper Citarik Sub Watershed, namely linear aspect (stream order, stream length, mean stream length, stream length ratio, bifurcation ratio, mean bifurcation ratio); areal aspect (drainage density, stream frequency, drainage texture, form factor, circularity ratio, elongation ratio, length of overland flow), and relief aspect (total basin relief, relief ratio). The results showed that the Upper Citarik Watershed consists of 17 Sub Watersheds. In general, all of the sub watersheds have an elongated watershed shape at high relief and relatively steep slope, volcanic rocks composition, and a slow rise in flooding. It indicates that the research area has relatively high resistance to potential flooding. As a catchment area in the Upper Citarum Watershed, it is better if the Upper Citarik Watershed is maintained in order to avoid various natural damages. Therefore, the condition of the Upper Citarik Sub Watershed requires sustainable conservation so that environmental damage does not occur which results in various disasters such as floods, landslides, and others.